Intra‐abdominal hemorrhage following 739 consecutive pancreaticoduodenectomy: Risk factors and treatments. Issue 6 (18th December 2018) - Lu, Jian‐Wen; Ding, Hong‐Fan; Wu, Xiao‐Ning; Liu, Xue‐Min; Wang, Bo; Wu, Zheng; Lv, Yi; Zhang, Xu‐Feng
Abstract: Background and Aim: Post‐pancreaticoduodenectomy hemorrhage (PPH) is a potentially lethal complication. The objective of this study was to explore the risk factors of PPH and to evaluate the treatment options. Methods: Clinical data of 739 consecutive patients undergoing pancreaticoduodenectomy between 2009 and 2017 were collected from a prospectively maintained database. Univariate and multivariate analysis was performed by logistic regression model to evaluate potential risk factors associated with early and late PPH. Results: The morbidity of PPH was 8.7% (64/739), while the mortality was 12.5% (8/64). Twenty‐two (34.4%) patients developed PPH within postoperative day 1 (early PPH) whereas 42 (65.6%) patients after postoperative day 1 (late PPH). No significant risk factor was identified associated with early PPH, whereas pancreatic duct diameter < 0.4 cm, and intra‐abdominal complications, such as pancreatic fistula, intra‐abdominal abscess, and delayed gastric emptying, were independently correlated with late PPH. There were 10 (15.6%) grade A, 28 (43.8%) grade B, and 26 (40.6%) grade C bleedings. The bleeding sites were verified by endoscopy, angiography, and/or exploratory laparotomy in 23 of 54 (42.6%) patients with grade B or C hemorrhage. Seven out of nine (78%) patients with arterial bleeding were cured by angiography and embolization, while 10 of 11 (90.9%) patients with anastomotic, venous, or retroperitoneum bleeding were rescued by laparotomy. Ten patients with grade A and 22 patients with grade B or C hemorrhage were treated successfully by blood transfusion and hemostatic medications. Conclusions: Hemorrhage following pancreaticoduodenectomy is a common and lethal complication. Treatment strategies should be tailored according to different etiologies.